Borderline conditions for single or platooning operations in freight transport on expressways: Case study in Japan - Kawasaki, Tomoya; Tagawa, Hoshi; Lau, Yui-yip (Frontiers in Future Transportation, 2022)
Truck platooning defines a convoy of freight vehicles using an electronic coupling system and has several advantages, particularly in terms of cost savings for fuel consumption and labor. Several issues are discussed for introducing platooning technology: the distance gap between trucks, number of trucks convoyed, waiting time at the platooning center, and origin and destination distance, which are influential variables on the transport costs. It is important to identify how these factors affect the boundary conditions for single or platooning freight transport operations. Therefore, this study aims to develop the cost function of platooning operations and compare transport costs between single and platooning operations, reveal influential factors on transport cost, and identify boundary conditions for single or platooning operations. The detailed cost functions in the conceptual network are developed considering the important factors affecting the transport cost. In the scenario analysis, the impacts of the vehicle distance gap and number of platooned trucks on the boundary conditions are further investigated. As a result, a comparative advantage of the platooning operation can be obtained with a shorter distance gap between vehicles. Specifically, as an example, when the distance gap is 49 m and OD distance is 800 km, the platooning operation is no longer an advantageous system with manned driving unless the waiting time at the platooning center is within 30 min. In addition, a platooning operation is feasible even with a transport distance of 100 km if trailing vehicles are driven by unmanned operations. The highest impact on cost reduction is the labor cost, which can significantly reduce the total transport costs.